2019
DOI: 10.1002/cam4.2139
|View full text |Cite
|
Sign up to set email alerts
|

Comparing high‐dose cisplatin with cisplatin‐based combination chemotherapy in definitive concurrent chemoradiation setting for locally advanced head and neck squamous cell carcinoma (LAHNSCC)

Abstract: Background High‐dose cisplatin (Cis) is a preferred systemic agent for concurrent chemoradiation (CRT) in locally advanced head and neck squamous cell cancer (LAHNSCC) patients. As some patients are unable to tolerate Cis, this study compares the toxicity and efficacy of weekly cisplatin‐paclitaxel (CP) regimen with Cis. Methods Patients with LAHNSCC receiving definitive chemoradiation either with Cis (Cisplatin—100 mg/m2 q3w x 3) or CP (Cisplatin—20 mg/m2; Paclitaxel—30 mg/m2qw x7) were included. Results Cis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
2
7
0
1
Order By: Relevance
“…A previous study compared cisplatin combined with paclitaxel to high-dose cisplatin in patients with locally advanced HNSCC receiving concurrent radiation. That study demonstrated less acute and chronic toxicities at one-fifth of the cisplatin dose with comparable overall survival rates and efficacy (10). In another study that followed patients with locally advanced HNSCC, induction chemotherapy combining docetaxel, cisplatin, and fluorouracil (TPF), in comparison to cisplatin and fluorouracil (PF), demonstrated significant improvement in overall-, median-and progression-free survival without increasing treatment-related toxicity, as measured by tracheostomies and dependence on gastric feeding tubes (18).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…A previous study compared cisplatin combined with paclitaxel to high-dose cisplatin in patients with locally advanced HNSCC receiving concurrent radiation. That study demonstrated less acute and chronic toxicities at one-fifth of the cisplatin dose with comparable overall survival rates and efficacy (10). In another study that followed patients with locally advanced HNSCC, induction chemotherapy combining docetaxel, cisplatin, and fluorouracil (TPF), in comparison to cisplatin and fluorouracil (PF), demonstrated significant improvement in overall-, median-and progression-free survival without increasing treatment-related toxicity, as measured by tracheostomies and dependence on gastric feeding tubes (18).…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, normal tissue and healthy cells throughout the body are also affected, resulting in one of the biggest patient-centered challenges with cisplatin: side effects. Not all patients will experience all of the known or listed side-effects, but some of the most common side-effects include nausea, vomiting, nephrotoxicity and ototoxicity, with the latter two being the most severe (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of surgical margins, extra-nodal extension, and perineural invasion are pathological features that describe the group of patients with a higher risk of recurrence. In these cases, radiotherapy and high doses of cisplatin-based chemotherapy improve patient survival [ 45 ]. Conversely, tumours at an advanced stage are commonly treated with CRT.…”
Section: Hncs Clinical Approachesmentioning
confidence: 99%